Managing Complexity Challenges for Industrial Engineering and Operations Management - Hernández, Cesáreo; López-Paredes, Adolfo; Pérez-Ríos, José M. (Lecture Notes in Management and Industrial Engineering, 2014)
This book presents papers by experts in the field of Industrial Engineering, covering topics in business strategy; modelling and simulation in operations research; logistics and production; service systems; innovation and knowledge; and project management. The focus of operations and production management has evolved from product and manufacturing to the capabilities of firms and collaborative management. Nowadays, Industrial Engineering is concerned with the study of how to design, modify, control and improve the performance of complex systems. It has extended its scope to any physical landscape populated by social agents. This raises a major challenge to Industrial Engineering:  managing complexity. This volume shows how experts are dealing with this challenge.